Preparation process of positive electrode slurry, positive electrode plate and battery

By adopting a preparation process with low solid content and low viscosity in the positive electrode slurry of lithium-ion batteries, combined with multiple and small amounts of mixing and dispersing steps, the problem that the positive electrode slurry in the prior art is difficult to achieve low surface density and high stability. Achieve battery performance with high rate charge and discharge and low charging time.

CN119447149APending Publication Date: 2025-02-14HUIZHOU EVE POWER CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411581250.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When the positive electrode slurry of the existing lithium-ion battery increases the charge and discharge rate, it is difficult to achieve low surface density and high stability, resulting in low manufacturingability and long charging time of the battery.

Method used

Through a new positive electrode slurry preparation process, a mixing process with low solid content (40-55%) and low viscosity (300-1500mPa·S) is adopted, and multiple mixing and dispersing steps are combined to ensure the binder and The conductive agent is uniformly coated on the surface of the positive electrode active material to improve the dispersion stability of the slurry.

Benefits of technology

The long-term dispersion stability of the cathode slurry is achieved under low solid content and low viscosity, avoiding heavy agglomeration and scratches during the coating process, and ensuring the good appearance and high-rate charging and discharging performance of the cathode sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005123736600000191
    Figure BDA0005123736600000191
  • Figure BDA0005123736600000201
    Figure BDA0005123736600000201
  • Figure BDA0005123736600000202
    Figure BDA0005123736600000202
Patent Text Reader

Abstract

According to the preparation process of the positive electrode slurry, the positive plate and the battery provided by the invention, under the specific preparation process, the positive electrode slurry can still realize long-term dispersion stability under the conditions of low solid content of 40-55% and low viscosity of 300-1500mPa. S. And by utilizing the positive electrode slurry, the coating with the single-side surface density of 10-50g / m < 2 > can be realized, and obvious scratches cannot be generated in the coating process, so that the positive electrode plate can be ensured to have good appearance and can be applied to the actual preparation and production of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to a preparation process of a positive electrode slurry, a positive electrode sheet and a battery. Background Art

[0002] With the application of lithium-ion batteries in the automotive industry, people require shorter charging time and stronger accelerated charging performance, so the high-rate charge and discharge performance of power batteries is increasingly required. For example, in some special-purpose vehicles, the rate requirement far exceeds the current level, requiring a charge and discharge rate of >100C. If lithium-ion batteries want to achieve such a high charge and discharge rate, the electrode thickness needs to be very thin and the surface density needs to be very small.

[0003] At present, the most widely used positive electrode slurry on the market is ternary positive electrode slurry. The solid content of conventional ternary positive electrode slurry is between 65% and 75%, and the viscosity is between 8000 and 15000 mPa.s. The lowest single-sided surface density that can be achieved by coating positive electrode slurry in existing industrial factories is about 60g / m 2 When the surface density is further reduced, a large number of scratches will appear on the pole piece, and it will also cause scratches on the extrusion coating die lip, resulting in very low manufacturability and inability to coat low surface density pole pieces. Summary of the invention

[0004] In order to solve the problems and deficiencies in the prior art, the present application provides a positive electrode slurry preparation process, a positive electrode sheet and a battery. Under the preparation process, the positive electrode slurry can achieve long-term dispersion stability at a low solid content of 40-55% and a low viscosity of 300-1500mPa·S. The positive electrode slurry can achieve a single-sided surface density of 10-50g / m 2 The coating can be carried out without obvious scratches during the coating process, so the positive electrode sheet can be guaranteed to have a good appearance and morphology, and can be applied to the preparation and production of actual lithium-ion batteries.

[0005] According to the first aspect of the present application, a preparation process of a positive electrode slurry is improved, comprising the following steps: S1. Mixing a binder with a first part of a first solvent to obtain a first mixed solution; performing low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15 to 30 rpm, the high-speed stirring linear velocity is 10 to 20 m / s, and the mixing time is 120 to 400 min; S2. Adding a liquid conductive agent to the first mixed solution and mixing to obtain a second mixed solution; performing low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15 to 30 rpm, the high-speed stirring linear velocity is 10 to 20 m / s, and the mixing time is 60 to 120 min; S3. Mixing a powder conductive agent with a second part of the first solvent to obtain a powder conductive agent mixed solution; adding the powder conductive agent mixed solution to the second mixed solution and mixing to obtain a main solution; performing low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15 to 30 rpm, the high-speed stirring linear velocity is 10 to 20 m / s, and the mixing time is 60 to 120 min. m / s, and the mixing time is 120-180min; S4. Mix the positive electrode active material with the first part of the main liquid to obtain a third mixed liquid; stir at a low speed during mixing, the low-speed stirring rate is 15-30rpm, and the mixing time is 120-165min; S5. Add the second part of the main liquid to the third mixed liquid and mix to obtain a fourth mixed liquid; stir at a low speed and a high speed at the same time during mixing, the low-speed stirring rate is 15-30rpm, the high-speed stirring linear speed is 10-20m / s, and the mixing time is 60-180min; S6. Add the third part of the main liquid to the fourth mixed liquid and mix to obtain a fifth mixed liquid; stir at a low speed and a high speed at the same time during mixing, the low-speed stirring rate is 15-30rpm, the high-speed stirring linear speed is 10-20m / s, and the mixing time is 60-180min; S7. Adjust the viscosity of the fifth mixed liquid to 300-1500mPa.s and the solid content to 40-55% to obtain a positive electrode slurry.

[0006] In the prior art, in order to improve the energy storage capacity of the battery, the surface density of the electrode is often increased. Increasing the solid content of the slurry is one of the main ways to increase the density of the positive electrode. Generally speaking, there is a certain relationship between the solid content and the viscosity. The higher the solid content, the higher the viscosity. Therefore, the current main research direction tends to increase the solid content and viscosity of the slurry. On the other hand, the viscosity and solid content of the slurry are important factors affecting its stability. Under high solid content and high viscosity, the stability of the slurry is often higher. If the solid content and viscosity of the slurry are to be further reduced, it is often not feasible to directly add solvents, because after the additional addition of solvents, the solid content and viscosity of the slurry are reduced, which will lead to poor stability of the slurry, which is not conducive to the further application of the slurry, such as the production of positive electrode sheets. Reagglomeration is prone to occur during the coating process, and coating scratches are caused.

[0007] At the same time, as a multi-component non-equilibrium system, the biggest problem of slurry is that the internal particles agglomerate due to electrostatic attraction, van der Waals force or hydrogen bonding, or settle under the action of gravity, thus affecting the dispersion uniformity and stability of the slurry. Therefore, in order to make a stable slurry, it is necessary to comprehensively consider the influence of multiple factors such as material properties, formula, mixing process, environment, etc.

[0008] In the positive electrode slurry preparation process provided in the present application, the binder and the conductive agent are first mixed in sequence by a wet method, and then the obtained main liquid is divided into three parts and mixed with the positive electrode active material in sequence, so that the binder molecules and the conductive agent molecules can be effectively coated on the surface of the positive electrode active material particles, so that the van der Waals force, electrostatic repulsion, steric repulsion and other interactions between the various micro-nano particles, polymer chains and solvents in the final slurry reach a higher stable state, that is, there is a suitable steric hindrance between the particles, and the attraction and repulsion reach a high equilibrium state, so that the slurry has a higher dispersion stability. In particular, the present application divides the main liquid into three parts and mixes them with the positive electrode active material in sequence, that is, through multiple small-scale mixing and dispersion, the binder and conductive agent molecules can be more fully and evenly attached to the surface of the positive electrode active material particles, which is beneficial to achieving a high balance between the components in the slurry, thereby forming a stable and uniform suspension system, so that the slurry still has good long-term stability at a lower solid content and lower viscosity, and can prevent re-agglomeration and scratches during the coating process, which is beneficial to the preparation of low surface density positive electrode sheets, thereby achieving the purpose of preparing high-rate fast-charging lithium batteries.

[0009] Among them, in the process of preparing the main liquid in the above steps S1 to S3, the mixing operations involved are all carried out at the same time with low-speed stirring and high-speed stirring. Low-speed stirring is mainly for macroscopic mixing of the slurry, that is, breaking up the large powder agglomerates in the solution and evenly distributing them in the solution in the form of fine powder agglomerates. High-speed stirring is mainly for microscopic mixing of the slurry, that is, further breaking up and homogenizing the fine powder agglomerates or solid particle agglomerates in the solution to obtain sufficiently fine solid particles, and evenly distributing them in the solution to achieve the effect of microscopic ultrafine dispersion and homogenization. In the process of successively mixing the binder, liquid conductive agent, and powder conductive agent to form the main liquid, low-speed stirring and high-speed stirring are carried out at the same time, that is, macroscopic dispersion and microscopic dispersion are carried out at the same time, which is conducive to uniformly mixing the binder, conductive agent, and solvent in the slurry to achieve the best dispersion effect. The shape of the paddle in the low-speed stirring is generally a twisted leaf shape, and the shape of the paddle in the high-speed stirring is generally a disc-shaped shape with teeth. Of course, the shape of the paddles for low-speed stirring and high-speed stirring can be adjusted according to specific circumstances. It should also be noted here that the type of conductive agent and the order of addition will also have a certain impact on the dispersion stability of the positive electrode slurry. In the positive electrode slurry system provided in the present application, by combining the liquid conductive agent with the powder conductive agent, and adding the liquid conductive agent first and then the powder conductive agent, this is more conducive to the uniform and stable dispersion of the two conductive agents in the slurry system provided in the present application, promoting the stability of the slurry while improving the conductivity of the slurry and the positive electrode sheets and batteries prepared using the slurry.

[0010] When the first part of the main liquid is mixed with the positive electrode active material at the beginning of step S4, because more positive electrode active materials are added at once, the slurry at this time is in the form of dough. Only low-speed stirring is used, which is beneficial for the slurry to be in the state of dough, so that the effective ingredients of the binder and the conductive agent in the main liquid are effectively and evenly coated on the surface of the positive electrode active material particles, thereby promoting the dispersion and stability of the slurry. If high-speed stirring is applied at the same time, the slurry is in the form of dough, the stirring resistance increases, and there are many large lumps in the slurry, and high-speed stirring cannot effectively break up the large lumps. In this way, even if stirring is continued for a long time, a molecular-level uniform mixture cannot be obtained, which is not conducive to the dispersion stability of the slurry. Applying high-speed stirring in the state of dough at the same time will easily cause greater damage to the equipment.

[0011] After a period of low-speed stirring in step S4, the second part of the main liquid and the third part of the main liquid are added and mixed in S5 and S6, respectively, by combining low-speed stirring and high-speed stirring. At this time, the large powder clumps in the solution have been broken up into smaller powder clumps. At the same time, low-speed stirring and high-speed stirring are performed to further shear and disperse, realizing molecular-level dispersion, so that the slurry can still achieve long-term dispersion stability at a lower solid content and lower viscosity.

[0012] Preferably, in S1-S3, when forming the main liquid, the feed mass ratio of the binder: liquid conductive agent: powder conductive agent: first solvent is 1.0-4.0: 10.0-30.0: 1.0-7.0: 15.0-85.0; wherein the total mass of the first solvent is the sum of the mass of the first part of the first solvent and the mass of the second part of the first solvent. The mass ratio of each material in the main liquid is controlled so that the slurry formed by the binder, conductive agent, and first solvent components is more uniform and stable, that is, the interaction force between the materials is maintained in a more stable state, forming a better molecular-level mixed suspension system, which is conducive to the long-term stability of the slurry.

[0013] Preferably, in S1 and S3, the first solvent comprises N-methylpyrrolidone.

[0014] Preferably, in S1, the binder includes polyvinylidene fluoride; in S2, the effective component of the liquid conductive agent includes carbon nanotubes; in S3, the powder conductive agent includes a carbon black conductive agent, and in S4, the positive electrode active material includes a ternary positive electrode active material. Using carbon nanotubes of the above diameter and length as the effective component of the liquid conductive agent and using a carbon black powder conductive agent in combination with the carbon nanotubes is conducive to forming a more compact conductive network in the slurry, promoting the conductive connectivity of the conductive agent in the positive electrode active material, and improving the conductivity of the positive electrode sheet.

[0015] Preferably, the carbon nanotubes have a diameter of 5 to 40 nm and a length of 20 to 300 μm. Carbon nanotubes of the above diameter and length effectively improve the conductivity of the positive electrode slurry while not being easily agglomerated or difficult to disperse in the positive electrode slurry, and can promote the dispersion stability of the positive electrode slurry.

[0016] Preferably, the carbon black conductive agent includes at least one of acetylene black, SP, and Ketjen black.

[0017] Preferably, the ternary positive electrode active material includes at least one of a nickel-cobalt-manganese positive electrode active material and a nickel-cobalt-aluminum positive electrode active material.

[0018] Preferably, the D50 of the positive electrode active material is 1-15 μm. The dispersion stability of the positive electrode slurry is also related to the particle size of the positive electrode active material, because the positive electrode active material accounts for the largest proportion of the effective components of the positive electrode slurry, and the dispersion stability of its particles determines the dispersion stability of the positive electrode of the positive electrode slurry. Controlling the D50 of the positive electrode active material within the above range is conducive to appropriate steric hindrance between the positive electrode active material particles, so that there is a stable interaction force between the particles, and at the same time, it can also make the positive electrode active particles have a stable interaction force with other materials in the slurry, forming a relatively stable suspension dispersion system.

[0019] Preferably, in S2, the solid content of the liquid conductive agent is 4.0-10.0%. Ensuring that the solid content of the liquid conductive agent is within a relatively low numerical range is conducive to uniformly dispersing the active ingredients of the liquid conductive agent in the slurry and improving the stability of the active ingredients of the liquid conductive agent in the slurry.

[0020] Preferably, in S3, the solid content of the main liquid is 8-16%.

[0021] Preferably, S4 is divided into three steps, and the specific operations are as follows: S4.1. First, stir at a low speed, the stirring rate is 15-20rpm, and the mixing time is 30-45min; S4.2. After step S4.1, scrape the slurry on the stirrer and continue to stir at a low speed, the stirring rate is 20-30rpm, and the mixing time is 45-60min; S4.3. After step S4.2, scrape the slurry on the stirrer and continue to stir at a low speed, the stirring rate is 20-30rpm, and the mixing time is 45-60min. When the first part of the main liquid is mixed with the positive electrode active material, because there are many solid particles of the positive electrode active material added at once, low-speed stirring and dispersion are carried out in three steps, which is conducive to the full wetting and dispersion of the positive electrode active material in the solution, so that the positive electrode active material, the binder and the conductive agent can achieve good macroscopic dispersion, which lays the foundation for the subsequent further slurry to achieve microscopic dispersion, that is, molecular-level dispersion.

[0022] Preferably, in S4, the mass ratio of the positive electrode active material to the main liquid is 1:0.2-1; the total amount of the main liquid is equal to the sum of the masses of the first part of the main liquid, the second part of the main liquid, and the third part of the main liquid.

[0023] Preferably, in S4, the mass proportion of the first part of the main liquid in the main liquid is 40-60%; in S5, the mass proportion of the second part of the main liquid in the main liquid is 20-30%; in S6, the mass proportion of the third part of the main liquid in the main liquid is 20-30%. The first part of the main liquid accounts for a larger proportion, which is conducive to fully wetting and dispersing the positive electrode active material and achieving a preliminary macroscopic uniform dispersion of the positive electrode active material. The second and third parts of the main liquid account for a smaller proportion, because the solid content in the slurry is already high at this time. Small amounts and multiple liquid-liquid mixing are conducive to further uniformity and dispersion of the components in the slurry, promote molecular-level dispersion, and are conducive to the long-term dispersion stability of low-solid content, low-viscosity positive electrode slurry.

[0024] Preferably, in S7, the viscosity and solid content of the fifth mixed liquid are adjusted by adding a second solvent; the second solvent comprises N-methylpyrrolidone.

[0025] Preferably, in S7, after adjusting the viscosity and solid content of the fifth mixed liquid, it is also necessary to perform iron removal treatment on it.

[0026] According to a second aspect of the present application, a positive electrode sheet is provided. When preparing the positive electrode sheet, the positive electrode slurry used is prepared by the above-mentioned positive electrode slurry preparation process; the surface density of the positive electrode sheet is 10 to 50 g / m 2 The positive electrode slurry prepared by the present application can remain stable and non-precipitating during long-term storage, and will not significantly re-agglomerate during low-area-density coating, nor will it cause obvious scratches during the coating process, and has a good appearance, so it can effectively achieve low-area-density positive electrode coating, improve the battery's charge and discharge rate, and reduce the battery's charging time.

[0027] Preferably, the surface density of the positive electrode sheet is 10 to 35 g / m 2 .

[0028] According to the third aspect of the present application, a battery is provided, comprising the above-mentioned positive electrode sheet. The battery prepared using the above-mentioned positive electrode sheet with lower surface density can achieve higher rate charge and discharge, greatly reducing the charging time of the battery.

[0029] Preferably, the battery further comprises a negative electrode sheet, the surface density of the negative electrode sheet is 5 to 17 g / m 2 .

[0030] Preferably, when preparing the negative electrode sheet, the negative electrode slurry preparation process used includes the following steps:

[0031] Step 1. Mix the thickener and solvent B-1 to obtain a main liquid B; perform low-speed stirring and high-speed stirring at the same time during the mixing, the low-speed stirring rate is 5 to 30 rpm, the high-speed stirring linear speed is 10 to 20 m / s, and the mixing time is 120 to 400 min; Step 2. Mix the powder conductive agent B and the negative electrode active material, and then add the first part of the main liquid B to continue mixing to obtain a first mixed liquid B; perform low-speed stirring during the mixing, the low-speed stirring rate is 10 to 30 rpm, and the mixing time is 120 to 165 min; Step 3. Add the second part of the main liquid B to the first mixed liquid B and mix to obtain a second mixed liquid Liquid B; performing low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15-30rpm, the high-speed stirring linear speed is 10-20m / s, and the mixing time is 30-60min; Step 4. Adding binder B to the second mixed liquid B and mixing to obtain a third mixed liquid B; performing low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15-30rpm, the high-speed stirring linear speed is 10-20m / s, and the mixing time is 30-90min; Step 5. Adjusting the viscosity of the third mixed liquid B to 300-1050mPa.s and the solid content to 30-40% to obtain a negative electrode slurry.

[0032] Preferably, in step 1, when forming the main liquid B, the feed mass ratio of thickener:solvent B-1 is 0.005-0.03:1.

[0033] Preferably, in step 1, the thickener includes a carboxymethyl cellulose thickener; in step 2, the powder conductive agent B includes a carbon black conductive agent; the negative electrode active material includes a graphite active material; in step 4, the binder B includes an LA series aqueous binder B, and the effective ingredients of the LA series aqueous binder B include polyacrylic acid compounds and acrylonitrile multipolymers.

[0034] Preferably, the carboxymethyl cellulose thickener includes at least one of carboxymethyl cellulose, sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

[0035] Preferably, the carbon black conductive agent includes at least one of acetylene black, SP, and Ketjen black.

[0036] Preferably, the graphite-based active material includes at least one of natural graphite and artificial graphite.

[0037] Preferably, the solid content of the LA series water-based binder B is 4-15%.

[0038] Preferably, the LA aqueous binder B includes at least one of LA132, LA133, and LA136.

[0039] Preferably, solvent B-1 comprises water.

[0040] Preferably, in step 2, the D50 of the negative electrode active material is 1 to 20 μm.

[0041] Preferably, in steps 1 to 2 and 4, the mass ratio of negative electrode active material: main liquid B: binder B: powder conductive agent B is 1: (0.2 to 0.8): (0.05 to 0.6): (0.005 to 0.05).

[0042] Preferably, in step 2, the mass proportion of the first part of the main liquid B in the main liquid B is 40-50%; the mass proportion of the second part of the main liquid B in the main liquid B is 50-60%.

[0043] Preferably, step 2 is divided into three steps, and the specific operations are as follows: step 2.1. First perform low-speed stirring, the low-speed stirring rate is 15-20rpm, and the mixing time is 30-45min; step 2.2. After step 2.1 is completed, scrape the slurry on the agitator and continue to stir at a low speed, the low-speed stirring rate is 20-30rpm, and the mixing time is 45-60min; step 2.3. After step 2.2 is completed, scrape the slurry on the agitator and continue to stir at a low speed, the low-speed stirring rate is 20-30rpm, and the mixing time is 45-60min.

[0044] Preferably, in step 5, the viscosity and solid content of the third mixed solution are adjusted by adding solvent B-2; the second solvent includes water.

[0045] Preferably, in step 5, after adjusting the viscosity and solid content of the third mixed liquid B, it is also necessary to perform iron removal treatment on it. DETAILED DESCRIPTION

[0046] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present application, rather than all of the embodiments.

[0047] Example 1

[0048] 1. Preparation of positive electrode slurry

[0049] The preparation of the positive electrode slurry in this embodiment follows the following steps:

[0050] S1. 2.2 parts of PVDF binder and 18.0 parts of N-methylpyrrolidone were mixed to obtain a first mixed solution; low-speed stirring and high-speed stirring were performed simultaneously during the mixing, the low-speed stirring rate was 20 rpm, the high-speed stirring linear speed was 15 m / s, and the mixing time was 260 min;

[0051] S2. 13.3 parts of the liquid conductive carbon nanotube dispersion (solid content 6%) was added to the first mixed solution to obtain a second mixed solution; low-speed stirring and high-speed stirring were performed simultaneously during the mixing, the low-speed stirring rate was 28 rpm, the high-speed stirring linear speed was 150 m / s, and the mixing time was 90 min;

[0052] S3. Mix 3.8 parts of powder conductive agent carbon black SP with 4.0 parts of N-methylpyrrolidone to obtain a powder conductive agent mixed liquid; add the powder conductive agent mixed liquid to the second mixed liquid and mix to obtain a main liquid; perform low-speed stirring and high-speed stirring at the same time during mixing, the low-speed stirring rate is 28rpm, the high-speed stirring linear speed is 15m / s, and the mixing time is 90min; the solid content of the main liquid obtained in this step is 16%;

[0053] S4. After mixing 120.4 parts of the positive electrode active material NCM532 with 16.5 parts of the first part of the main solution (accounting for 40% of the mass of the main solution), wherein the D50 of the positive electrode active material is 7 μm, the following three steps are performed in sequence:

[0054] S4.1 firstly performs low-speed stirring, the low-speed stirring rate is 17 rpm, and the mixing time is 48 min;

[0055] S4.2. After step S4.1 is completed, the slurry on the stirrer is scraped off and continued to stir at a low speed, the low-speed stirring rate is 25 rpm, and the mixing time is 50 min;

[0056] S4.3. After step S4.2 is completed, the slurry on the stirrer is scraped off and then the low-speed stirring is continued. The low-speed stirring rate is 25 rpm and the mixing time is 50 min.

[0057] S5. 12.4 parts of the second main liquid (accounting for 30% of the mass of the main liquid) were added to the third mixed liquid to obtain a fourth mixed liquid; low-speed stirring and high-speed stirring were performed simultaneously during mixing, the low-speed stirring rate was 28 rpm, the high-speed stirring linear speed was 15 m / s, and the mixing time was 120 min;

[0058] S6. 12.4 parts of the third main liquid (accounting for 30% of the mass of the main liquid) were added to the fourth mixed liquid to obtain a fifth mixed liquid; low-speed stirring and high-speed stirring were performed simultaneously during the mixing, the low-speed stirring rate was 28 rpm, the high-speed stirring linear speed was 15 m / s, and the mixing time was 120 min;

[0059] S7. The viscosity of the fifth mixed solution is adjusted to 480 mPa.s and the solid content is adjusted to 54.3%. After filtering and removing iron, a positive electrode slurry is obtained.

[0060] In the above steps S4 to S6, the mass ratio of the positive electrode active material to the main liquid is 1:0.34.

[0061] 2. Preparation of batteries

[0062] (1) Preparation of positive electrode

[0063] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.5 g / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0064] (2) Preparation of negative electrode sheet

[0065] The surface density of this embodiment is 15.8 g / m 2 A negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance and no scratches.

[0066] In the negative electrode sheet of this embodiment, the preparation process of the negative electrode slurry used includes the following steps:

[0067] Step 1. Mix 0.29 parts of thickener carboxymethyl cellulose with 39 parts of water to obtain main liquid B; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 17 rpm, the high-speed stirring linear speed is 15 m / s, and the mixing time is 260 min;

[0068] Step 2. Mix 0.60 parts of powder conductive agent carbon black SP and 96.3 parts of negative electrode active material artificial graphite, then add 21.6 parts of the first part of main liquid B (accounting for 55% of the mass of main liquid B) and continue mixing to obtain a first mixed liquid B, in which the D50 of the negative electrode active material is 6 μm; during mixing, perform the following three steps in sequence:

[0069] Step 2.1. First, perform low-speed stirring, the low-speed stirring rate is 17 rpm, and the mixing time is 38 min;

[0070] Step 2.2. After step 2.1, scrape the slurry on the stirrer and continue stirring at a low speed, the stirring rate is 25 rpm, and the mixing time is 67 min;

[0071] Step 2.3. After step 2.2, scrape the slurry on the stirrer and continue stirring at a low speed, the stirring rate is 25 rpm, and the mixing time is 68 min;

[0072] Step 3. Add 17.7 parts of the second main liquid B (accounting for 45% of the mass of the main liquid B) to the first mixed liquid B to obtain a second mixed liquid B; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 23 rpm, the high-speed stirring linear speed is 15 m / s, and the mixing time is 45 min;

[0073] Step 4. Add 10.2 parts of binder B LA132 (solid content 6%) to the second mixed solution B to obtain a third mixed solution B; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 22 rpm, the high-speed stirring linear speed is 15 m / s, and the mixing time is 60 min;

[0074] Step 5. The viscosity of the third mixed solution B is adjusted to 822 mPa.s and the solid content is 36%. After filtering and removing iron, the negative electrode slurry is obtained.

[0075] (3) Battery assembly

[0076] The positive electrode sheet, separator and negative electrode sheet are assembled in sequence, the obtained battery cell is placed in a shell, and the electrolyte is injected, formed, and constant volume is obtained to obtain a battery. The formula of the electrolyte is as follows: 1 mol / L LiPF6 ethylene carbonate EC+diethyl carbonate DEC+dimethyl carbonate DMC (volume ratio 1:1:1).

[0077] Example 2

[0078] 1. Preparation of positive electrode slurry

[0079] The preparation of the positive electrode slurry in this embodiment is different from that in embodiment 1 in that the total number of parts of the main liquid is 45 parts, that is, the mass ratio of the main liquid to the positive electrode active material is 0.37:1. Specifically, 2.0 parts of PVDF binder and 18 parts of N-methylpyrrolidone are used in S1, 14.8 parts of carbon nanotube dispersion liquid as liquid conductive agent are used in S2, and 4.5 parts of carbon black SP powder conductive agent and 6.0 parts of N-methylpyrrolidone are used in S3, and the solid content of the main liquid is finally obtained to be 15.8%; in S4-S6, the amount of the first part of the main liquid is still 40% of the mass of the main liquid, the amount of the second part of the main liquid is still 30% of the mass of the main liquid, and the amount of the third part of the main liquid is still 30% of the mass of the main liquid; and finally, after adjusting the viscosity and solid content of the fifth mixed liquid in S7, the viscosity of the positive electrode slurry is 593mPa.s and the solid content is 53.3%. The rest of the operations are consistent with embodiment 1.

[0080] 2. Preparation of batteries

[0081] (1) Preparation of positive electrode

[0082] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.6 g / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0083] (2) Preparation of negative electrode sheet

[0084] The surface density of this embodiment is 15.8 g / m 2 A negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance and no scratches.

[0085] In the negative electrode sheet of this embodiment, the preparation process of the negative electrode slurry used is consistent with that of Embodiment 1.

[0086] (3) Battery assembly

[0087] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0088] Example 3

[0089] 1. Preparation of positive electrode slurry

[0090] The preparation of the positive electrode slurry in this embodiment is different from that in Example 1 in that the total number of parts of the main liquid is 96.5 parts, that is, the mass ratio of the positive electrode active material to the main liquid is 1:0.80. Specifically, in the process of preparing the main liquid in S1-S3, 1.9 parts of the binder PVDF and 30.1 parts of N-methylpyrrolidone are used in S1, 16.4 parts of the liquid conductive agent carbon nanotube dispersion are used in S2, and 5.1 parts of the powder conductive agent carbon black SP and 43 parts of N-methylpyrrolidone are used in S3, and the solid content of the main liquid is finally obtained to be 8%; and in S4-S6, the amount of the first part of the main liquid added is 60% of the mass of the main liquid, the amount of the second part of the main liquid added is still 20% of the mass of the main liquid, and the amount of the third part of the main liquid added is still 20% of the mass of the main liquid; and finally, after adjusting the viscosity and solid content of the fifth mixed liquid in S7, the viscosity of the positive electrode slurry is 506mPa.s and the solid content is 52.4%. The rest of the operations are consistent with Example 1.

[0091] 2. Preparation of batteries

[0092] (1) Preparation of positive electrode

[0093] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.5 g / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0094] (2) Preparation of negative electrode sheet

[0095] The surface density of this embodiment is 15.8 g / m 2 A negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance and no scratches.

[0096] In the negative electrode sheet of this embodiment, the preparation process of the negative electrode slurry used is consistent with that of Example 1.

[0097] (3) Battery assembly

[0098] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0099] Example 4

[0100] 1. Preparation of positive electrode slurry

[0101] The preparation of the positive electrode slurry in this embodiment is different from that in Example 1 in that the total number of parts of the main liquid is 104.8 parts, that is, the mass ratio of the positive electrode active material to the main liquid is 1:0.87. Specifically, in the process of preparing the main liquid in S1-S3, 1.8 parts of the binder PVDF and 28.2 parts of N-methylpyrrolidone are used in S1, 18 parts of the liquid conductive agent carbon nanotube dispersion are used in S2, and 5.8 parts of the powder conductive agent carbon black SP and 51 parts of N-methylpyrrolidone are used in S3, and the solid content of the main liquid is finally obtained to be 8%; and in S4-S6, the amount of the first part of the main liquid added is 60% of the mass of the main liquid, the amount of the second part of the main liquid added is still 20% of the mass of the main liquid, and the amount of the third part of the main liquid added is still 20% of the mass of the main liquid; and finally, after adjusting the viscosity and solid content of the fifth mixed liquid in S7, the viscosity of the positive electrode slurry is 524mPa.s and the solid content is 47%. The rest of the operations are consistent with Example 1.

[0102] 2. Preparation of batteries

[0103] (1) Preparation of positive electrode

[0104] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.5 g / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0105] (2) Preparation of negative electrode sheet

[0106] The surface density of this embodiment is 15.8 g / m 2 A negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance and no scratches.

[0107] In the negative electrode sheet of this embodiment, the preparation process of the negative electrode slurry used is the same as that of Embodiment 1.

[0108] (3) Battery assembly

[0109] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0110] Example 5

[0111] 1. Preparation of positive electrode slurry

[0112] The preparation of the positive electrode slurry in this embodiment is different from that in Example 1 in that, in the process of preparing the main solution in S1 to S3, the binder PVDF used in S1 is 0.5 parts, and the amount of the other materials used to prepare the main solution is consistent with that in Example 1; the solid content of the main solution is finally 12.3%; and after adjusting the viscosity and solid content of the fifth mixed solution in S7, the viscosity of the positive electrode slurry is 471mPa.s and the solid content is 48.4%. The rest is the same as in Example 1.

[0113] 2. Preparation of batteries

[0114] (1) Preparation of positive electrode

[0115] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.5 g / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0116] (2) Preparation of negative electrode sheet

[0117] The surface density of this embodiment is 15.8 g / m 2 A negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance and no scratches.

[0118] In the negative electrode sheet of this embodiment, the preparation process of the negative electrode slurry used is consistent with that of Example 1.

[0119] (3) Battery assembly

[0120] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0121] Example 6

[0122] 1. Preparation of positive electrode slurry

[0123] The preparation of the positive electrode slurry in this embodiment is different from that in Example 1 in that, in the process of preparing the main solution in S1 to S3, the liquid conductive agent carbon nanotube dispersion liquid used in S1 is 17 parts, and the amount of materials used to prepare the main solution is consistent with that in Example 1; the solid content of the main solution is finally 15.0%; and after adjusting the viscosity and solid content of the fifth mixed solution in S7, the viscosity of the positive electrode slurry is 485mPa.s and the solid content is 48%. The rest is the same as in Example 1.

[0124] 2. Preparation of batteries

[0125] (1) Preparation of positive electrode

[0126] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.5 g / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0127] (2) Preparation of negative electrode sheet

[0128] The surface density of this embodiment is 15.8 g / m 2 A negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance and no scratches.

[0129] In the negative electrode sheet of this embodiment, the preparation process of the negative electrode slurry used is consistent with that of Example 1.

[0130] (3) Battery assembly

[0131] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0132] Example 7

[0133] 1. Preparation of positive electrode slurry

[0134] The preparation of the positive electrode slurry in this embodiment is different from that in Example 1 in that the three-step mixing is not performed in S4, but directly in one step, specifically: after mixing 120.4 parts of the positive electrode active material NCM532 with 16.5 parts of the first part of the main liquid (accounting for 40% of the mass of the main liquid), stirring is performed at a low speed of 25 rpm for 148 minutes; and after adjusting the viscosity and solid content of the fifth mixed liquid in S7, the viscosity of the positive electrode slurry is 597 mPa.s and the solid content is 51.4%. The rest is the same as in Example 1.

[0135] 2. Preparation of batteries

[0136] (1) Preparation of positive electrode

[0137] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.5 g / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0138] (2) Preparation of negative electrode sheet

[0139] The surface density of this embodiment is 15.8 g / m 2 A negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance and no scratches.

[0140] In the negative electrode sheet of this embodiment, the preparation process of the negative electrode slurry used is consistent with that of Example 1.

[0141] (3) Battery assembly

[0142] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0143] Example 8

[0144] 1. Preparation of positive electrode slurry

[0145] The preparation of the positive electrode slurry in this embodiment is different from that in Example 1 in that the material ratios in the preparation of the main liquid are consistent with those in Example 1, but in S4-S6, only 24.2 parts of the main liquid are weighed and mixed with 120.4 parts of the positive electrode active material NCM532, that is, the mass ratio of the positive electrode active material to the main liquid is 1:0.1, and in S4-S6, the amount of the first part of the main liquid added is still 40% of the mass of the main liquid, the amount of the second part of the main liquid added is still 30% of the mass of the main liquid, and the amount of the third part of the main liquid added is still 30% of the mass of the main liquid; and finally, after adjusting the viscosity and solid content of the fifth mixed liquid in S7, the viscosity of the positive electrode slurry is 468mPa.s and the solid content is 52.8%. The rest is the same as in Example 1.

[0146] 2. Preparation of batteries

[0147] (1) Preparation of positive electrode

[0148] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.5 g / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0149] (2) Preparation of negative electrode sheet

[0150] The surface density of this embodiment is 15.8 g / m 2 A negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance and no scratches.

[0151] In the negative electrode sheet of this embodiment, the preparation process of the negative electrode slurry used is consistent with that of Example 1.

[0152] (3) Battery assembly

[0153] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0154] Example 9

[0155] 1. Preparation of positive electrode slurry

[0156] The preparation of the positive electrode slurry in this embodiment is different from that in Example 1 in that the total number of parts of the main liquid is 144.5 parts, that is, the mass ratio of the main liquid to the positive electrode active material is 1:1.2. Specifically, in the process of preparing the main liquid in S1-S3, 2.0 parts of the binder PVDF and 32 parts of N-methylpyrrolidone are used in S1, 14.8 parts of the liquid conductive agent carbon nanotube dispersion are used in S2, and 4.5 parts of the powder conductive agent carbon black SP and 91.1 parts of N-methylpyrrolidone are used in S3; in S4-S6, the amount of the first part of the main liquid added is still 40% of the mass of the main liquid, the amount of the second part of the main liquid added is still 30% of the mass of the main liquid, and the amount of the third part of the main liquid added is still 30% of the mass of the main liquid; the solid content of the main liquid finally obtained is 9.0%; and after adjusting the viscosity and solid content of the fifth mixed liquid in S7, the viscosity of the positive electrode slurry is 732mPa.s and the solid content is 49.8%. The rest is the same as Example 1.

[0157] 2. Preparation of batteries

[0158] (1) Preparation of positive electrode

[0159] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.5 / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0160] (2) Preparation of negative electrode sheet

[0161] The surface density of this embodiment is 15.8 g / m 2 A negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance and no scratches.

[0162] In the negative electrode sheet of this embodiment, the preparation process of the negative electrode slurry used is consistent with that of Example 1.

[0163] (3) Battery assembly

[0164] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0165] Comparative Example 1

[0166] 1. Preparation of positive electrode slurry

[0167] The preparation of the positive electrode slurry in this comparative example follows the following steps:

[0168] S1. 2.2 parts of PVDF binder and 18 parts of N-methylpyrrolidone were mixed to obtain a first mixed solution; low-speed stirring and high-speed stirring were performed simultaneously during the mixing, the low-speed stirring rate was 20 rpm, the high-speed stirring linear speed was 15 m / s, and the mixing time was 260 min;

[0169] S2. 13.3 parts of the liquid conductive carbon nanotube dispersion were added to the first mixed solution to obtain a second mixed solution; low-speed stirring and high-speed stirring were performed simultaneously during the mixing, the low-speed stirring rate was 28 rpm, the high-speed stirring linear speed was 15 m / s, and the mixing time was 90 min;

[0170] S3. Mix 3.8 parts of powder conductive agent carbon black SP with 4.0 parts of N-methylpyrrolidone to obtain a powder conductive agent mixed liquid; add the powder conductive agent mixed liquid to the second mixed liquid and mix to obtain a main liquid; perform low-speed stirring and high-speed stirring at the same time during mixing, the low-speed stirring rate is 28rpm, the high-speed stirring linear speed is 15m / s, and the mixing time is 90min; the solid content of the main liquid obtained in this step is 16%;

[0171] S4. 120.4 parts of the positive electrode active material NCM532 were mixed with the main liquid (all the main liquid), and low-speed stirring was first performed, the low-speed stirring time was 25 rpm, and the mixing time was 148 min; then low-speed stirring and high-speed stirring were performed simultaneously, the low-speed stirring rate was 28 rpm, the high-speed stirring linear speed was 15 m / s, and the mixing time was 240 min;

[0172] S6. The viscosity of the fourth mixed solution is adjusted to 850 mPa.s and the solid content is adjusted to 47.2%. After filtering and removing iron, a positive electrode slurry is obtained.

[0173] 2. Preparation of batteries

[0174] (1) Preparation of positive electrode

[0175] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.5 g / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0176] (2) Preparation of negative electrode sheet

[0177] The surface density of this comparative example is 15.8 g / m 2 A negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance with slight scratches.

[0178] In the negative electrode sheet of this comparative example, the preparation process of the negative electrode slurry used is consistent with that of Example 1.

[0179] (3) Battery assembly

[0180] The battery assembly in this comparative example is consistent with that in Example 1.

[0181] Comparative Example 2

[0182] 1. Preparation of positive electrode slurry

[0183] The difference between this comparative example and Example 1 is that only low-speed stirring is used in S5 and S6, that is, S5 and S6 do not apply low-speed stirring and high-speed stirring at the same time, but only apply low-speed stirring; finally, in S7, the viscosity of the fifth mixed liquid is adjusted to 1055mPa.s, and the solid content is 44.1%. After filtering and removing iron, the positive electrode slurry is obtained.

[0184] 2. Preparation of batteries

[0185] (1) Preparation of positive electrode

[0186] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.5 g / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0187] (2) Preparation of negative electrode sheet

[0188] The surface density of this comparative example is 15.8 g / m 2 The negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance but severe scratches.

[0189] In the negative electrode sheet of this comparative example, the preparation process of the negative electrode slurry used is consistent with that of Example 1.

[0190] (3) Battery assembly

[0191] The battery assembly in this comparative example is consistent with that in Example 1.

[0192] Comparative Example 3

[0193] 1. Preparation of positive electrode slurry

[0194] The difference between this comparative example and Example 1 is that the liquid conductive agent carbon nanotube dispersion, the powder conductive agent carbon black SP, and N-methylpyrrolidone are added at one time and mixed with the first mixed liquid, and low-speed stirring and high-speed stirring are performed simultaneously during mixing, the low-speed stirring rate is 28 rpm, the high-speed stirring linear speed is 15 m / s, and the mixing time is 180 min; finally, the solid content and viscosity of the positive electrode slurry are adjusted to be consistent with Example 1; the rest is consistent with Example 1.

[0195] 2. Preparation of batteries

[0196] (1) Preparation of positive electrode

[0197] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 28.5 g / m 2At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0198] (2) Preparation of negative electrode sheet

[0199] The surface density of this comparative example is 15.8 g / m 2 A negative electrode sheet (obtained by adjusting the coating parameters), and at this surface density, the negative electrode sheet has a good appearance with slight scratches.

[0200] In the negative electrode sheet of this comparative example, the preparation process of the negative electrode slurry used is consistent with that of Example 1.

[0201] (3) Battery assembly

[0202] The battery assembly in this comparative example is consistent with that in Example 1.

[0203] Comparative Example 4

[0204] 1. Preparation of positive electrode slurry

[0205] This comparative example directly uses a commercially available conventional ternary positive electrode slurry (NCM811), wherein the viscosity is 3800 mPa.s and the solid content is 74%.

[0206] 2. Preparation of batteries

[0207] (1) Preparation of positive electrode

[0208] The positive electrode slurry prepared above was coated on the positive electrode current collector (aluminum foil), and the coating parameters were adjusted so that the surface density of the final positive electrode sheet was 70 g / m 2 At this surface density, the positive electrode sheet has a good appearance and no scratches.

[0209] (2) Preparation of negative electrode sheet

[0210] This comparative example uses commercially available 2 The negative electrode sheet has good appearance and no scratches at this surface density.

[0211] (3) Battery assembly

[0212] The battery assembly in this comparative example is consistent with that in Example 1.

[0213] Test Case

[0214] 1. Experimental Construction Method

[0215] (1) Cathode slurry performance test

[0216] The viscosity and solid content of the positive electrode slurry prepared in all the above embodiments and comparative examples are statistically analyzed, and the solid content fluctuation value of the positive electrode slurry is calculated after storage for 24 hours. The calculation formula is as follows: solid content fluctuation value = solid content of the lower layer after storage of the positive electrode slurry - solid content of the positive electrode slurry before storage for 24 hours. Regarding the solid content of the lower layer after the positive electrode slurry is stored for 24 hours, this means, for example, that the positive electrode slurry is placed in a beaker, and after storage for 24 hours, the positive electrode slurry at the bottom of the beaker is taken for testing; and regarding the solid content before storage of the positive electrode slurry, this means, for example, that the positive electrode slurry is placed in a beaker, and the positive electrode slurry has just been stirred and mixed evenly, and the positive electrode slurry at any part of the beaker can be taken for solid content testing.

[0217] (2) Positive electrode performance test

[0218] The surface density of the positive electrode sheets prepared in all the above embodiments and comparative examples was statistically analyzed, and the appearance of the positive electrode sheets obtained after coating was observed.

[0219] (3) Battery performance test

[0220] The batteries prepared in all the above embodiments and comparative examples were tested for cycle capacity retention at discharge rates of 1C, 10C, 30C, 50C, 70C, and 100C, respectively. The specific charge and discharge test operation is as follows: Under a 25°C environment, the divided battery is charged to 4.2V with a 1C constant current and constant voltage, the cut-off current is 0.02C, and left for 5 minutes, and then discharged to 3.0V with 1C, 10C, 30C, 50C, 70C, and 100C, respectively. The capacity retention rate is calculated as follows: Taking the 1C discharge capacity as the benchmark, the discharge capacity at each rate is divided by the benchmark capacity.

[0221] Meanwhile, the DCR (direct current resistance) test was performed on the batteries prepared in all the above embodiments and comparative examples. The specific test method is as follows: after 6000 cycles, discharge at 1C for 10S at 50% SOC, and calculate △V / △I.

[0222] 2. Experimental results

[0223] The relevant performance test results of the positive electrode slurries, positive electrode sheets and batteries prepared in all the above embodiments and comparative examples are shown in Tables 1 and 2.

[0224] Table 1 Performance test results of positive electrode slurry and positive electrode sheet in the embodiments and comparative examples

[0225]

[0226]

[0227] Table 2 Performance test results of batteries in the examples and comparative examples

[0228]

[0229] As can be seen from Tables 1 and 2, the slurry prepared by the pulping process of the present application has the characteristics of low viscosity and low solid content, and the slurry has good stability, which can ensure low surface density coating while maintaining a good electrode appearance. The battery prepared using the above-mentioned low-surface-density positive electrode has good fast charging performance, and still has a high capacity retention rate after charging and discharging at a high rate, and has a low resistance, thereby greatly optimizing the fast charging performance of the battery. Please refer to the performance data in Examples 1 to 9 for details.

[0230] In comparative example 1, the main liquid is not mixed in steps, but directly mixed in one step; in comparative example 2, S4, S5, and S6 are all stirred at low speed; in comparative example 3, liquid conductive agent and powder conductive agent are added simultaneously; in comparative example 4, a conventional commercially available ternary positive electrode slurry is used, which has high solid content, high viscosity, and high pole sheet surface density. The above reasons all lead to a decrease in the storage stability of the positive electrode slurry (the solid content fluctuation value is large after 24 hours), and the slurry material is not dispersed or re-agglomerated after dispersion. Therefore, some positive electrode sheets prepared by roller pressing have light scratches or severe scratches and other poor coating appearance problems, resulting in a significant decrease in the capacity retention rate of the battery at a larger rate (such as 70C and 100C), and the DCR of the battery is also significantly increased, and the fast charging performance is poor. In particular, it can also be seen that the high-viscosity and high-solid content slurry in comparative example 4 cannot achieve the coating of low-surface-density pole sheets, and it is impossible to prepare low-surface-density positive electrode sheets.

[0231] Further observation of Examples 1 to 4 and Examples 8 to 9 shows that when the mass ratio of the positive electrode active material to the main liquid or the solid content of the main liquid in the process of preparing the positive electrode slurry is changed, although the viscosity, solid content, storage stability, etc. of the positive electrode slurry are not much different, it will have a certain impact on the capacity retention rate of the battery prepared using it at a higher rate. The battery prepared in Example 1 has better overall performance.

[0232] Comparing Example 1 with Examples 5 and 6, the amount of binder used in Example 5 is relatively small, while the amount of liquid conductive agent used in Example 6 is relatively large, both of which lead to a slight decrease in the capacity retention rate of the battery at a higher rate. This shows that in the process of preparing the positive electrode slurry, the usage ratio of each material has a certain influence on the stability of the slurry positive electrode or the conductive network. At a specific material usage, the electrochemical properties of the battery, such as the fast charging performance, will be better.

[0233] Comparing Example 1 with Example 7, in Example 7, S4 does not include three steps of low-speed stirring, but directly performs mixing in one step, which results in a decrease in the storage stability of the positive electrode slurry and a decrease in the capacity retention rate of the battery at a higher rate.

[0234] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.

Claims

1. A process for preparing a positive electrode slurry, characterized in that: The following steps are involved: S1. Mixing the binder with the first part of the first solvent to obtain a first mixed solution; performing low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15 to 30 rpm, the high-speed stirring linear speed is 10 to 20 m / s, and the mixing time is 120 to 400 min; S2. Adding a liquid conductive agent to the first mixed solution and mixing to obtain a second mixed solution; performing low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15 to 30 rpm, the high-speed stirring linear speed is 10 to 20 m / s, and the mixing time is 60 to 120 min; S3. Mixing the powder conductive agent with the second part of the first solvent to obtain a powder conductive agent mixed solution; adding the powder conductive agent mixed solution to the second mixed solution to obtain a main solution; performing low-speed stirring and high-speed stirring at the same time during mixing, the low-speed stirring rate is 15 to 30 rpm, the high-speed stirring linear speed is 10 to 20 m / s, and the mixing time is 120 to 180 min; S4. The positive electrode active material is mixed with the first part of the main liquid to obtain a third mixed solution; the mixing is performed at a low speed, the low speed stirring rate is 15 to 30 rpm, and the mixing time is 120 to 165 min; S5. The second part of the main liquid is added to the third mixed liquid to obtain a fourth mixed liquid; low-speed stirring and high-speed stirring are performed simultaneously during mixing, the low-speed stirring rate is 15 to 30 rpm, the high-speed stirring linear speed is 10 to 20 m / s, and the mixing time is 60 to 180 min; S6. Add the third part of the main liquid to the fourth mixed liquid to obtain a fifth mixed liquid; while mixing, low-speed stirring and high-speed stirring are performed simultaneously, the low-speed stirring rate is 15 to 30 rpm, the high-speed stirring linear speed is 10 to 20 m / s, and the mixing time is 60 to 180 min; S7. Adjust the viscosity of the fifth mixed solution to 300-1500 mPa.s and the solid content to 40-55% to obtain the positive electrode slurry.

2. The process for preparing the positive electrode slurry according to claim 1, characterized in that: In S1 to S3, when the main liquid is formed, the feed mass ratio of the binder: the liquid conductive agent: the powder conductive agent: the first solvent is 1.0 to 4.0: 10.0 to 30.0: 1.0 to 7.0: 15.0 to 85.0; wherein the total mass of the first solvent is the sum of the masses of the first part of the first solvent and the second part of the first solvent.

3. The process for preparing the positive electrode slurry according to claim 1, characterized in that: In S1, the binder includes polyvinylidene fluoride; In said S2, the effective ingredients in said liquid conductive agent include carbon nanotubes; In S3, the powder conductive agent includes a carbon black conductive agent; In S4, the positive electrode active material includes a ternary positive electrode active material.

4. The process for preparing the positive electrode slurry according to claim 3, characterized in that: In S2, the solid content of the liquid conductive agent is 4.0-10.0%.

5. The process for preparing the positive electrode slurry according to claim 1, characterized in that: In S3, the solid content of the main liquid is 8-16%.

6. The process for preparing the positive electrode slurry according to claim 1, characterized in that: The S4 is divided into three steps, and the specific operations are as follows: S4.

1. Firstly, stir at a low speed of 15 to 20 rpm and for a mixing time of 30 to 45 min; S4.

2. After step S4.1 is completed, the slurry on the stirrer is scraped off and continued to stir at a low speed, the low-speed stirring rate is 20 to 30 rpm, and the mixing time is 45 to 60 min; S4.

3. After step S4.2 is completed, scrape the slurry on the stirrer and continue stirring at a low speed. The low-speed stirring rate is 20 to 30 rpm and the mixing time is 45 to 60 minutes.

7. The process for preparing the positive electrode slurry according to claim 1, characterized in that: In S4 to S6, the mass ratio of the positive electrode active material to the main liquid is 1:0.2 to 1; The total amount of the main liquid is equal to the sum of the masses of the first part of the main liquid, the second part of the main liquid, and the third part of the main liquid.

8. The process for preparing the positive electrode slurry according to claim 7, characterized in that: In S4, the mass proportion of the first part of the main liquid in the main liquid is 40-60%; In S5, the mass proportion of the third part of the main liquid in the main liquid is 20-30%; In S6, the mass proportion of the third part of the main liquid in the main liquid is 20-30%.

9. A positive electrode sheet, characterized in that: When preparing the positive electrode sheet, the positive electrode slurry used is prepared by the positive electrode slurry preparation process according to any one of claims 1 to 8; The surface density of the positive electrode sheet is 10 to 50 g / m 2 .

10. A battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 9.